Electrochemical Characterization of the Repurposed Antimicrobial Compound Auranofin in Aqueous Solutions. Issue 5 (11th January 2022) - Yossief, Melak; Singh, Vikram; Maydaniuk, Dustin; Cardona, Silvia; Kuss, Sabine
Abstract: Electrochemical sensors are gaining attention for the detection and quantification of pharmaceuticals in the environment. To that end, there is an interest in understanding the electrochemical characteristics of drugs. Herein, the multi‐purpose drug auranofin is investigated for the first time in aqueous media. This compound offers therapeutic benefits in strains of cancer, parasites, bacteria and fungi, which have grown immune to many antibiotics. Auranofin detection was optimized at carbon black‐modified electrodes. Voltammetry provides information about redox potentials, levels of detection and quantification, and pH dependence. Parameters identified in this study will be useful for auranofin sensing in environmental samples, and for studies related to drug resistance. Abstract :